Avaliação de ecossistemas degradados pela ação antrópica no município de Morros - MA - Muniz, Eliana Maria (1999)
This study sought to evaluate some of the causes that led to the municipality of Morros to present a high degree of poverty and environmental degradation, and have indicators of low quality standards of life of families in the rural area of ​​the municipality. were selected for the study three villages, which have characteristics similar to those prevailing throughout the municipality, in which 71 families were interviewed, distributed as follows: 27 families in Bom Gosto village, 15 families in Bom Princípio village and 29 families in the Mato Grosso village. The information collection instruments were basically structured questionnaires, containing questions related to the condition of family life and related to production, also using semi-structured interviews, carried out with some older people who had knowledge about the advancement of devastation and vegetation cover existing in the municipality previously. As a complement, we sought evaluate the physical and chemical characteristics of the soils worked by farmers, with soil profiles being made in the areas under study. The samples of Collected soils were analyzed in the UEMA soil laboratory. The results found in the research point to the characterization families in the villages as having minimal access to medical care and very critical levels of education. They also point to the existence of precarious housing conditions, and farmers do not own the land where they work. The basic agricultural product is cassava, which is used to make flour, which provides them with a very low income. It was also observed that farmers are degrading their environment, their workplace and their place of survival. This is because, as a result of the deep state of poverty that could be observed through the research, they intensively use natural resources until they are exhausted, without having as their main concern the preservation of the environment. Furthermore, a reduction was observed in the period in which farmers leave the lands they have worked fallow, precisely in view of the current stage of degradation in which most areas located in Morros are found. Since there is a strong relationship between poverty and environmental degradation, it is necessary to implement public policy interventions that enable the generation of activities that improve the quality of life of families in a state of poverty such as those who survive in Morros. These policies could seek to employ both agricultural and non-agricultural activities. In fact, it is observed that the municipality of Morros has a considerable potential for ecological tourism, but that it is not being properly exploited. There is potential for agricultural activities that regenerate the soil, with the cultivation of perennial crops, intercropped with annual crops, provided that technical and economic feasibility studies are carried out for the implementation of these activities. In the short term, it is believed that activities capable of generating income and employment for the people of Morros should be created, and environmental education campaigns should be initiated for the farmers of Morros, showing them the difficulties they will face as a consequence of the inadequate way in which they are using their land.